2019
DOI: 10.1101/657114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Layer 6 ensembles can selectively regulate the behavioral impact and layer-specific representation of sensory deviants

Abstract: Predictive models can enhance the salience of unanticipated input, and the neocortical laminar architecture is believed to be central to this computation. Here, we examined the role of a key potential node in model formation, layer (L) 6, using behavioral, electrophysiological and imaging methods in mouse somatosensory cortex. To test the contribution of L6, we applied weak optogenetic drive that changed which L6 neurons were sensory-responsive, without affecting overall firing rates in L6 or L2/3. This stimul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…Because GCaMP expression is limited to upper L6 in Ntsr1-Cre 3 Ai148 mice and because these CT cells have sparse, slender, and short apical dendritic and axonal fields ( Figure 1A), there is very little out-of-plane fluorescence, permitting two-photon calcium imaging at depths of $0.7 mm without using high excitation laser power ( Figure 4C). 5,22,34,35 In agreement with our phototagged recordings, we found that L6 CT neurons were strongly recruited by orofacial movements, where the activity rates of 74% of cells was significantly changed from baseline, mostly reflecting enhanced activity beginning prior to lick spout contact (n = 739, N = 3; Figure 4D).…”
Section: Motor-preparatory Inputs Activate L6 Ct Ensemblessupporting
confidence: 86%
See 1 more Smart Citation
“…Because GCaMP expression is limited to upper L6 in Ntsr1-Cre 3 Ai148 mice and because these CT cells have sparse, slender, and short apical dendritic and axonal fields ( Figure 1A), there is very little out-of-plane fluorescence, permitting two-photon calcium imaging at depths of $0.7 mm without using high excitation laser power ( Figure 4C). 5,22,34,35 In agreement with our phototagged recordings, we found that L6 CT neurons were strongly recruited by orofacial movements, where the activity rates of 74% of cells was significantly changed from baseline, mostly reflecting enhanced activity beginning prior to lick spout contact (n = 739, N = 3; Figure 4D).…”
Section: Motor-preparatory Inputs Activate L6 Ct Ensemblessupporting
confidence: 86%
“…The advent of optogenetic approaches to activate and silence layer 6 corticothalamic (L6 CT) neurons in Ntsr1-Cre transgenic mice reinvigorated research on corticofugal circuits, inspiring new hypotheses about their role in sensory gain control and predictive coding. [2][3][4][5][6][7] Optogenetic stimulation or inactivation of Ntsr1-Cre+ neurons has demonstrated that L6 CTs are not subtle modulators of downstream activity, but instead throttle the excitability of thalamic and cortical circuits through their direct connections onto combinations of excitatory and inhibitory cell types in each brain region. [2][3][4][8][9][10][11][12][13] Conventional optogenetic stimulation induces artificial patterns of spatiotemporal activity that do not resemble natural spiking, but these experiments can identify testable hypotheses about the type of firing patterns that might be naturally employed during particular behavioral states.…”
Section: In Briefmentioning
confidence: 99%
“…Because they are spatially intermingled with other L6 cell types, and because of the strong reciprocal connectivity of the thalamus and cortex, traditional methods for in vivo neural recordings, stimulation or inactivation have made it challenging to identify a specific role for L6 CTs in sensory processing. The advent of optogenetic approaches to activate and silence genetically targeted L6 CT neurons in Ntsr1-Cre transgenic mice has reinvigorated research on CT circuits, inspiring new hypotheses about their role in sensory gain control and predictive coding (Crandall et al, 2015;Gong et al, 2007;Guo et al, 2017;Olsen et al, 2012;Vélez-Fort et al, 2014;Voigts et al, 2019;Williamson and Polley, 2019). However, any role for L6 CTs in active sensing has been purely speculative, as targeted recordings from L6 CTs have never been made in behaving animals.…”
Section: Main Textmentioning
confidence: 99%
“…3B-C (Fig. 1A), there is very little out of plane fluorescence, permitting 2-photon calcium imaging at depths of ~0.7mm without using high excitation laser power (Daigle et al, 2018;Liang et al, 2019;Voigts et al, 2019) (Fig. 4C).…”
Section: Motor-related Inputs From Orofacial Movements -But Not Locommentioning
confidence: 99%
See 1 more Smart Citation